Hubungan Karakteristik Penjamu dan Breeding Place dengan Kejadian DBD Di Kabupaten Serdang Bedagai - Hetti Citra Marbun; Sri Malem Indirawati; Nurmaini Nurmaini (Syntax Idea, 2021)
DBD (Dengue Hemorrhagic Fever) is atransmitted disease caused by dengue virus and transmitted by Aedes aegypti mosquito. There were 183 cases of DBD in Serdang Bedagai Regency with one of them died in 2019 (Incidence Rate of 29.6 per 100,000 inhabitants and CFR = 0,5). The objective of the research was to analyze the correlation of age factor (0 months - 17 years) and breeding places with the incidence of DBD in children in Serdang Bedagai Regency, in 2020. The research used observational analytic method with case control design. The samples were 24 respondents in the case group and 24 respondents in the control group. The data were gathered by conducting observation and interviews and analyzed by using univariate analysis and bivariate analysis with chi square test. The result of bivariate analysis showed that there was the correlation of using mosquito coils at (OR= 4,580), behavior of combating mosquito breeding place at (OR= 3,100) and breeding places at (OR = 4,000) with the incidence of DBD. Meanwhile, there is no correlation of age at (p=1,000) and gender at (p= 0,511) with the incidence of DBD. So, that it is recommended that people of Serdang Bedagai Regency always use mosquito repellent at home but is not recommended to use mosquito coils because it is not environmentally friendly and people should use lotion, electric, spraying and preferably at home using gauze. Reducing water reservoirs, drain TPA routinely, and eradicating mosquito nests once a week.